Modeling recast layer and surface finish in the manufacturing of high–aspect ratio micro-tools using the inverse slab electrical discharge milling process. (April 2014) - Gil, R; Sánchez, Jose A; Plaza, S; Ortega, N; Izquierdo, B; Pombo, I
Electrical discharge milling–based processes are a good alternative for the manufacturing of micro-tools. However, some limitations must be considered both on the fields of process cost and control of surface characteristics. The inverse slab electrical discharge milling (ISEDM) process is an economic alternative to other high-precision high-cost machining processes because a conventional slab electrical discharge milling (SEDM) machine can be used to produce high–aspect ratio cylindrical tools with diameters as low as 200 µm. In this article, the influence of process variables on the surface integrity generated by the ISEDM process is presented. An experimental model aiming at the prediction of both surface finish and thickness of the recast layer as a function of the spark characteristics is developed. The influence of process variables is then analyzed. The model was validated with a high degree of agreement by carrying out experimental tests on submicron sintered high-speed steel micro-pins. Micro-tools with a diameter 335 µm and an aspect ratio as high as 90:1 can be manufactured using this novel technique with a surface finish below Ra 0.7 µm and thickness of recast layer below 3 µm.